Policy Implementation of Lembah Putri Beach Tourism Development in Putrapinggan Village, Pangandaran Regency - Mona Indrianie; Rifqi Kahirul Arifin (Formosa Journal of Multidisciplinary Research, 2023)
Implementation of the Policy for Development of the Lembah Putri Beach Tourism Object in Putrapinggan Village, Pangandaran Regency. The aim of this research was to find out the implementation of the Policy for Development of the Lembah Putri Beach Tourism Object and to find out the supporting and inhibiting factors in implementing the policy.This study is analyzed using policy theory that focuses on policy implementation from George C. Edward III which consists of communication indicators, resource indicators, disposition indicators, and bureaucratic structure indicators. In this study using a qualitative descriptive method, namely the type of research that seeks to describe the object or subject under study in accordance with what it is. Data collection techniques in this study were carried out by interviews, observation, literature study, and documentation. As well as data analysis used using memos, coding, and transcripts. Based on the research results obtained, it can be seen that the Implementation of Policy for Development of the Lembah Putri Tourism Object has not been implemented optimally, there are perceived obstacles such as: There is still a low level of human resources who have knowledge in the field of tourism and do not yet have inter-sectoral functions.